On the multiplication and convolution of homogeneous distributions (1990)
We investigate several notions of the multiplicative, resp. the convolution product, in the case of both factors being homogeneous distributions. Explicit criteria for the existence of some of these products are given under the assumption that one of the factors is C∞ outside the origin